Design and Development Artificial Heart Valve - Jasim, Ali Mohammed; jabbar, Mohammed Rashid; khalf, Tabark adnan; hilo, Ali kareem (American Journal of Biomedicine and Pharmacy, 2025)
Design of an artificial heart valve (case study) using (SOLIDWORKS) based on international standards and measurements. The type of valve was chosen from among the many known types based on several studies, including the study of characteristics and the uses of each type. The studies included field visits to the specialized cardiology centers, including Ibn al- Bitar Hospital, and to see the cases of common injuries and damage that occur in the natural heart valves. We achieved several answers from them. Type of artificial valve (Mechanical bileaflets valve) was chosen according to the mentioned studies. These studies also included (study of the blood flow in each type and the effect of the material on the body on the body and its compatibility with the daily routine of the person). the material was strong, durable, fatigue resistant and biocompatible. Also, other properties like the hydrophobic property and others. It is worth noting that our choice of this type does not mean the inefficiency of the other heart valves. However, this valve was chosen based on its special characteristics and its need in the daily routine of the patient. According to the experts, Mitral Valve damage is the most common in Iraq, and the best choice for replacement is the (Mechanical Bileaflet Valve).